Effect of membrane system configuration on the performance of polysulfone hollow fiber membrane system for CO2/CH4 separation - Yaacob, N.; Ismail, Ahmad Fauzi (Universiti Teknologi Petronas, 2004)
In this study we focused on the effect of one- and two-stage membrane system configurations in series arrangement for the CO2/CH4 separation. Asymmetric polysulfone hollow fiber membranes were fabricated from 33%wt of polysulfone polymer using a simple dry/wet phase inversion process. Interestingly, the pressure normalized flux of CO2 was decreased with increasing of the membrane stages. In addition, the selectivities of the asymmetric hollow fiber membrane showed a more constant trend with increasing of' feed pressure. Between the two configurations, two-stage membrane configuration showed the most constant trend of, selectivity values. This results confirmed that the two stage membrane configuration posses a significant influence on gas transport properties which lead to better selectivity values. The effect of stage cut on membrane system configurations was also investigated. This study suggested that the best CO2/CH4 separation was achieved by using two-stage membrane system configuration.